Leadership of Chairmen of Civic Assemblies ways to build skills and culture of communication - Shakarov Akmal (International Consortium of Education and Culture Research Studies, 2019)
This paper makes analyses of the leadership of Chairmen of Civic Assemblies . On this points, ways to build skills and culture of communication of the points were stated to make deep investigates. Make research points to make further detailed analyses on this topic.